Euro area countries and the efficiency of ECB monetary policy with regard to the principles of OCA - Machala, Martin; Durčáková, Jaroslava, 1941-; Čermáková, Daniela; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The main aim of the Thesis is to prove a hypothesis if monetary policy of the European Central Bank is suitable for all members of the Euro zone. The theoretical part of this thesis is devoted to the position, goals, and tools used by the European Central Bank, which are bound to the development of monetary policy. The main tool of the analysis is the optimum currency area theory. The theory compares the inflation of the Member countries, with the monetary policy of the European Central Bank. In the long term, the inflation of the Euro zone countries, which currently are in major economic problems, differed from the average inflation of the Euro zone. From the results of the analysis, it is recognizable that there is very slow rate of the convergence in inflation. The convergence in inflation is an important condition of creating an optimal currency area. As a result, countries, which are in main economic problems, need to adjust other channels as exchange rate is fixed. For that reason, a common monetary policy of the European Central Bank for all countries of the Euro zone is not always optimal.
Vedoucí práce: Jaroslava Durčáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; finance and accounting for common europe [obor dipl. práce]